Migration and the rural-urban continuum: evidence from Bukidnon, Philippines - Quisumbing, Agnes R.; McNiven, Scott (2006)
This paper explores the heterogeneity of the migrant experience using the Bukidnon Panel Survey, which follows up 448 families in rural Mindanao who were first interviewed in 1984-85, as well as their offspring. Migration patterns are examined using the full listing of children of the original respondents as well as a special survey including 257 of the migrant offspring who were tracked down and interviewed in 2004. The migrant survey focuses on differences in the migration experience of males and females who migrated to rural, poblacion, and urban areas. The study finds that rural areas, poblaciones, and urban areas systematically attract different types of migrants. It also finds that the most important determinants of an individual`s location decision are life-cycle effects, specifically marriage and educational attainment.